Democracy without Coercion: A Social Utopia? - Vasiliauskaitė, Nida (Problemos, 2006)
The article deals with the understanding of the relationship between coercion and rationality in contemporary political philosophy and with the postmodern conception of democracy. In the first part, the failure to construct the model of a non-coercive social order based on a rational consensus and the “utopicity” of the idea is discussed, while the second part draws on the postmodern notion of political utopia. The author aims to show that postmodern anti-utopianism is often understood too straightforwardly and simplistically. Such inadequate understanding leads to incorrect reproaches for incoherence, when the supposed utopian contraimplications are uncovered.
Keywords: democracy; coercion; rationality; justice; utopia